2020
DOI: 10.1039/d0nr04581k
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-responsive chiral self-sorting in amyloid-inspired minimalistic peptide amphiphiles

Abstract: Self-sorting is a spontaneous phenomenon that ensures formation of complex yet ordered multicomponent system and conceptualizes the design of artificial and orthogonally functional compartments. In the present study, we envisage...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Chiral selectivity is ubiquitous in nature, so it is expected that proteins and peptides tend to prefer homochiral molecular interactions. Studies of L - and D -stereoisomers of amyloid peptides, such as a 22-residue segment of β 2 -microglobulin and β-amyloid peptide (Aβ40), showed that amyloid fibril formation was stereospecific: L -enantiomer was deposited on L -seeds, and enantiomers did not cross-react with each other ( Esler et al, 1999 ; Wadai et al, 2005 ; Gupta et al, 2020 ). However, it has been demonstrated that mixing enantiomers can change the kinetics, morphology, and mechanical properties of peptide self-assemblies ( Nagy-Smith et al, 2017 ; McAulay et al, 2019 ; Bera et al, 2020 ; Qin et al, 2021 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…Chiral selectivity is ubiquitous in nature, so it is expected that proteins and peptides tend to prefer homochiral molecular interactions. Studies of L - and D -stereoisomers of amyloid peptides, such as a 22-residue segment of β 2 -microglobulin and β-amyloid peptide (Aβ40), showed that amyloid fibril formation was stereospecific: L -enantiomer was deposited on L -seeds, and enantiomers did not cross-react with each other ( Esler et al, 1999 ; Wadai et al, 2005 ; Gupta et al, 2020 ). However, it has been demonstrated that mixing enantiomers can change the kinetics, morphology, and mechanical properties of peptide self-assemblies ( Nagy-Smith et al, 2017 ; McAulay et al, 2019 ; Bera et al, 2020 ; Qin et al, 2021 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…86,87 The properties of these materials depends on the length, composition, and sequence of peptides, 86 but is also strongly affected by the chirality of the amino acids and by the nature of the aromatic groups. [88][89][90][91][92][93][94][95][96] Such supramolecular self-assembly involves β-sheets formation and different type of arrangement are proposed: parallel, antiparallel or interlocked anti-parallel (Fig. 4).…”
Section: Effect Of Aromatics On Peptide Self-assemblymentioning
confidence: 99%
“…If monomers of one enantiomer forms fibrils, it is typically observed that monomers of the other are unable to be incorporated into these mirror‐image seeds. Such enantioselective fibril growth has been established in a number of systems including β2‐microglobulin fragments, [30–32] amyloid β peptides, [31, 33, 34] and other short amyloidogenic peptides [28, 35, 36] . PolyQ peptides seem to be an exception to this rule [37] …”
Section: Figurementioning
confidence: 99%
“…Such enantioselective fibril growth has been established in a number of systems including β2‐microglobulin fragments,[ 30 , 31 , 32 ] amyloid β peptides,[ 31 , 33 , 34 ] and other short amyloidogenic peptides. [ 28 , 35 , 36 ] PolyQ peptides seem to be an exception to this rule. [37] …”
mentioning
confidence: 96%